2005
DOI: 10.1111/j.1439-037x.2004.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming Increases Crop Yield Possibly by Modulating Enzymes of Sucrose Metabolism in Chickpea

Abstract: The number of seeds and seed yield per plant were higher in chickpea crops raised from water and mannitol (4 %) primed seeds in comparison with the control non-primed crops. In primed plants, an enhanced acid invertase activity in the apical part of the main stem and the part immediately below it at 100 and 130 days after sowing (DAS) might result in an increased availability of hexoses to these plant parts. In addition, decreased acid invertase activity at the point of initiation of branches and in the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 29 publications
4
61
0
Order By: Relevance
“…Moreover, under salinity stress, KNO 3 prevents salinity build-up in plant tissues because K + counteracts the harmful effects of Na + toxicity. 29,30 Priming chickpea seeds with mannitol promoted seedling growth 31 and crop yield 32 under water deficit by enhancing enzymes in sucrose metabolism. Similar promotive effects were also reported in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, under salinity stress, KNO 3 prevents salinity build-up in plant tissues because K + counteracts the harmful effects of Na + toxicity. 29,30 Priming chickpea seeds with mannitol promoted seedling growth 31 and crop yield 32 under water deficit by enhancing enzymes in sucrose metabolism. Similar promotive effects were also reported in rice.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of priming included faster emergence of crop seedlings, early flowering and higher grain yield even under drought stress (Kaur et al, 2005). In sunflower, osmopriming with KNO 3 and hydropriming improved the germination and stand establishment under stress conditions (Kaya et al, 2006).…”
Section: Seed Primingmentioning
confidence: 99%
“…Comparing the mean of the effects of interplay (Figure 2) showed that the longest (1.02 cm) and shortest (0.44 cm) seedling length observed for 24 hours seed priming with boric acid 1.5% and control (without priming) concentration, respectively. Material transport in primed seeds is high because of higher activity of enzymes involved in sucrose metabolism (sucrose synthase, invertase, sucrose phosphate synthase), so these seeds have higher biological power and germinate quicker and produce plumule and radicle, so clearly have a higher seedling length (Kaur et al, 2005).…”
Section: Seedling Lengthmentioning
confidence: 99%